A Review of Consumer Embarrassment as a Public and Private Emotion - Krishna, Aradhna; Herd, Kelly B.; Aydınoğlu, Nilüfer Z. (Journal of Consumer Psychology, 2019)
Whether the result of mispronouncing a fancy brand name, miscalculating a tip, purchasing a sensitive product, or stumbling into a product display, embarrassment is an important part of the consumer landscape. Embarrassment has traditionally been considered a social emotion, one that can only be experienced in public. In this paper, we offer a comprehensive review of consumer embarrassment and consider situations in which embarrassment can affect consumer behavior in both public and private contexts. We define embarrassment using this broader conceptualization and outline the transgressions that might trigger embarrassment in consumption contexts. We also discuss the diverse implications of embarrassment for consumer behavior, and review the strategies that both consumers and practitioners can use to mitigate embarrassment and its negative consequences. We hope this framework will stimulate new research on consumer embarrassment in both public and private contexts.